Identification of a regulatory element for yeast tryptophan permease Tat2 ubiquitination using high hydrostatic pressure. Issue 2 (3rd April 2019) - Ishii, Ryoga; Aramaki, Mari; Mochizuki, Takahiro; Abe, Fumiyoshi
ABSTRACT: Tryptophan uptake in the yeast Saccharomyces cerevisiae is extremely sensitive to high pressure; therefore, the growth of tryptophan auxotrophic strains is impaired. Degradation of tryptophan permease Tat2 is enhanced at 25 MPa, depending on Rsp5 ubiquitin ligase. Any defect in Tat2 ubiquitination confers high pressure growth capacity, which is a luminous phenotype of the yeast used to explore the mechanism by which Rsp5 mediates Tat2 ubiquitination. Here we show that the N-terminal four (K17, K20, K29, and K31) among five lysines are required for efficient Tat2 degradation under high pressure. We found that a domain spanning D70 to S76 is also critical for Tat2 degradation at 25 MPa probably because of the recognition by Bul1, an adaptor protein of Rsp5. Defects in Tat2 ubiquitination do not produce any remarkable mutant phenotype at 0.1 MPa. Therefore, we suggest that high pressure is a unique and advanced tool to explore ubiquitination-dependent Tat2 regulation.